2019
DOI: 10.1002/jsfa.10080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in ovo feeding of β‐hydroxy‐β‐methylbutyrate on hatchability, muscle growth and performance in prenatal and posthatch broilers

Abstract: BACKGROUND β‐Hydroxy‐β‐methylbutyrate (HMB) is the metabolite of leucine that plays an important role in muscle protein metabolism. The objective of the present study was to determine the effects of in ovo feeding (IOF) of HMB at 7 days of incubation (DOI) via air cell or 18 DOI via amnion on hatchability, muscle growth and performance in prenatal and posthatch broilers. RESULTS IOF of HMB via air cell at 7 DOI increased hatchability by 4.34% compared with the control (89.67% versus 85.33%). Birds in IOF group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…A previous study reported that the growth-promoting effect of IOF of β-hydroxy-β-methyl butyrate decreased gradually with the increasing age (28) . In contrast, another study had shown that the weight advantage caused by IOF Accepted manuscript could be sustained to D 42 at least (29) . In this study, we found that IOF of vitamin C significantly increased the splenic vitamin C content on D 21, but there was no significant difference on D 42.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study reported that the growth-promoting effect of IOF of β-hydroxy-β-methyl butyrate decreased gradually with the increasing age (28) . In contrast, another study had shown that the weight advantage caused by IOF Accepted manuscript could be sustained to D 42 at least (29) . In this study, we found that IOF of vitamin C significantly increased the splenic vitamin C content on D 21, but there was no significant difference on D 42.…”
Section: Discussionmentioning
confidence: 93%
“…The time of injection is determined by the type of compounds and the desired output to bring in the embryos. As HMB helps in forming the first generation of myoblasts and this formation occurs around 7 ED, injection of HMB into air cell on ED 7 showed more beneficial effect than injection into embryonic amnion on ED 18 ( 29 ).…”
Section: Routes and Time Of In Ovo Deliverymentioning
confidence: 99%
“…A significantly lower level of lipid and CORT indicates adaptation to HS. Dietary supplementation of beta-hydroxy-betamethylbutyrate (HMB), a leucine metabolite, can act as a precursor of beta-hydroxy-betamethylglutaryl coenzyme-A (HMG-CoA) and contributes to cholesterol synthesis, which is required for maximal cell functions and cell growth (29,103). It decreases chicken mortality, increases carcass yield, and improves protein metabolism in muscle in case of attenuating proteolysis (104).…”
Section: Amino Acids and Their Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations